Merging Formality and Informality in Dispute Resolution - Wada, Y (Victoria University of Wellington Law Review, 1997)
From a legal sociologist's perspective of focusing on the views of the participants themselves, this article considers the various positions adopted with respect to Alternative Dispute Resolution, identifies unexplored issues, and argues that a dynamic view of dispute resolution implies the need for considerable fusion of formal and informal aspects in almost all dispute resolution processes.